Results from the Survey of Antibiotic Resistance (SOAR) 2011-13 in Turkey - ALTINKANAT GELMEZ, GÜLŞEN (OXFORD UNIV PRESS, 2016)
Objectives: Data are presented from the Survey of Antibiotic Resistance (SOAR) for respiratory tract infection pathogens collected in 2011-13 from Turkey. Methods: MICs were determined using Etest (R). Susceptibilitywas assessed using CLSI, EUCASTand pharmacokinetic/pharmacodynamic (PK/PD) interpretive criteria. Results: Rates of antibiotic susceptibility were very low among 333 isolates of Streptococcus pneumoniae tested: penicillin 38% using CLSI (oral) and EUCAST breakpoints; erythromycin 51% using CLSI and EUCAST criteria; and cefuroxime 64.6% using CLSI and PK/PD and 46.9% using EUCAST. Of the isolates, >90% were susceptible to amoxicillin/clavulanic acid, ceftriaxone (except using EUCAST criteria: 76%), levofloxacin and high-dose intravenous penicillin. Among 339 Haemophilus influenzae isolates, 6.8% were beta-lactamase positive while 9.1% were beta-lactamase negative but ampicillin resistant (BLNAR) by CLSI (14.7% by EUCAST) criteria. Amoxicillin/clavulanic acid susceptibility was similar to 90% by CLSI (with or without BLNAR adjustment, EUCAST and high-dose PK/PD) but lower, at 82.9%, by EUCAST with BLNAR adjustment. Levofloxacin susceptibility was 96% using all three breakpoints. Dramatic differences in rates of susceptibility, depending on the breakpoints used, were seen for cefaclor [ 94% by CLSI (86.4% BLNAR adjusted), 23% by PK/PD] and cefuroxime [97% by CLSI (89.1% BLNAR adjusted), 85% by PK/PD, 15% by EUCAST (13.0% BLNAR adjusted)]. Streptococcus pyogenes (n = 222) and Moraxella catarrhalis (n = 40) isolates remained highly susceptible to amoxicillin/clavulanic acid, cephalosporins and levofloxacin, with only erythromycin susceptibility dropping below 95% for S. pyogenes. Conclusions: Overall, amoxicillin/clavulanic acid and levofloxacin were themost active antibiotics based on all three breakpoints against these pathogens. Although susceptibility was not universally low in Turkey, high resistance rates were found in S. pneumoniae and, when using PK/PD and EUCAST breakpoints, in other respiratory pathogens.
Keywords: COMMUNITY-ACQUIRED PNEUMONIA; HAEMOPHILUS-INFLUENZAE; STREPTOCOCCUS-PNEUMONIAE; ANTIMICROBIAL RESISTANCE; MORAXELLA-CATARRHALIS; MACROLIDE RESISTANCE; EUROPE; PYOGENES; ADULTS